Correlations between different manifestation of speed in elite female volleyball - Iordache, G.; Stoica, M.; Costache, R.; Dina, G. (Science, Movement & Health, 2026)
Aim. The aim of this study was to investigate the relationships between different forms of speed—reaction speed, movement speed, and vertical jump performance—in elite junior female volleyball players. Methods. The study employed an observational research design and included 11 Romanian female athletes, all members of the U17 national volleyball national team. Reaction speed and movement speed were assessed using the Witty system, while vertical jump performance (as an indicator of explosiveness) was evaluated using the OptoJump system. Data analysis was conducted using descriptive statistics and Spearman`s rank correlation coefficient to examine the relationships between the analyzed variables. Results. The results indicated no statistically significant correlations between reaction speed, movement speed, and vertical jump performance (p > 0.05), suggesting that these forms of speed function independently in elite junior female volleyball players. Conclusions. The findings highlight that reaction speed, movement speed, and vertical jump explosiveness represent distinct motor qualities that should be developed through specific and targeted training methods. These results support the implementation of individualized physical training programs tailored to the performance demands of youth high performance volleyball.